Implementation of the Preventation of Human Trafficking Policy based on Stakeholders Synergy (Study at the Dinas Sosial Kabupaten Malang) - Hutri Agustino (Universitas Muhammadiyah Malang, 2022)
Social policy is a form of public policy which is a government decision made to respond to issues of a public nature, namely overcoming social problems or meeting the needs of the public at large. Social policy is also a provision designed collectively to prevent social problems (preventive function), overcome social problems (curative function) and promote welfare (development function) as a form of state obligation in fulfilling the rights of its citizens. In other terms, social policy can be said to be a social aspect, that is, something related to the field of social welfare. Social policies are the principles, procedures and procedures of existing laws, which serve as administrative and regulatory guidelines for institutions that affect public welfare. By using a qualitative approach with a descriptive type, the research conducted at the Malang Regency Social Service found that there were various stakeholders involved in various preventive, rehabilitative and prosecution efforts against the perpetrators of the crime of human trafficking. But the results have not been optimal due to several main things, including the absence of a Regional Regulation that explicitly discusses anti-human trafficking. In addition, the commitment of local governments to human resource development, especially targeting vulnerable socio-economic groups to become victims of the criminal act of trafficking in persons, is still not maximal.